KARAKTERISASI MORFOLOGI KETAHANAN KEKERINGAN PLASMA NUTFAH PADI GOGO LOKAL ASAL SULAWESI TENGGARA - Sadimantara, Gusti Ray; Muhidin, Muhidin (Jurnal Agroteknos, 2012)
Efforts to increase rice production to achieve sustainable production faced a serious challenge. Rice demand is increasing due to population growth, changing consumption patterns of non-rice to rice, and the improvement of the local economy. On the other hand the national rice production is more limited. One alternative way to secure national rice production is through development of sub-optimal land, in the form of dry land, for upland rice cultivation. Potency of dry land for upland rice is big enough though constrained by such factors of soil fertility, rainfall and the presence of blast attacks. Test for drought stress was conducted using the Standard Evaluation System (SES) for Rice developed by the International Rice Researh Institute (IRRI). The results of the study on 24 local upland rice cultivars, based on the degrees of curl leaf and shoot dry index, it was known that there were two varieties that are very resistant to drought stress, i.e. cultivar Sala Bali and cultivar Wangkariri, and as many as six cultivars i.e. Paebiu Kolopua, Paebiu Tamalaki, Wangko'ito, and Wa Mengkale that were resistant to drought. Keyword: drought resistant, germplasm, upland rice